The Psychology and Physiology of Reaching a Healthy Weight. - Calcagno, Cheri (Health psychology collection., 2015)
Over the years while teaching weight management classes for hospitals and corporations, my interest moved from that of the physical to include more of the mind. I began to realize that people can know what they need to do to be healthy, but doing it is an entirely different ball game. Educating people who are in bondage with bad habits often results in them being smarter, but not necessarily healthier. As I got more involved with coaching people individually, I learned there were deep dimensions to a person's health behaviors. Forming relationships with clients who trusted me enough to share the intimate details of their lives helped me understand how marvelously complex creating change can and must be for that change to be sustained. We have so many needs and layers to our being, which all impact our behavior. I found that to have the most impact, I had to work with the person as a whole and help them explore each part--body, mind, and spirit. Within the spirit lies the way you feel about your life and whether you love, or even like, yourself. To truly improve life and become better means developing each of your parts and appreciating that they come together to make you the beautiful person you are.